Nonparametric estimation of a conditional quantile function in a fixed effects panel data model - Karen X. Yan; Qi Li (Journal of Risk and Financial Management, 2018)
This paper develops a nonparametric method to estimate a conditional quantile function for a panel data model with an additive individual fixed effects. The proposed method is easy to implement, it does not require numerical optimization and automatically ensures quantile monotonicity by construction. Monte Carlo simulations show that the proposed estimator performs well in finite samples.
Keywords: C14; C21; 330; nonparametric method; conditional quantile function; panel data